How do you factor \[2{x^2} + 8x + 8 = 0\]?
Answer
Verified
442.8k+ views
Hint: A polynomial of degree two is called a quadratic polynomial and its zeros can be found using many methods like factorization, completing the square, graphs, quadratic formula etc. The quadratic formula is used when we fail to find the factors of the equation. If factors are difficult to find then we use Sridhar’s formula to find the roots. That is \[x = \dfrac{{ - b \pm \sqrt {{b^2} - 4ac} }}{{2a}}\].
Complete step-by-step solution:
Given, \[2{x^2} + 8x + 8 = 0\]
Since the degree of the equation is 2, we have 2 factors.
On comparing the given equation with the standard quadratic equation\[a{x^2} + bx + c = 0\], we have\[a = 2\], \[b = 8\] and \[c = 8\].
The standard form of the factorization of quadratic equation is \[a{x^2} + {b_1}x + {b_2}x + c = 0\], which satisfies the condition \[{b_1} \times {b_2} = a \times c\] and \[{b_1} + {b_2} = b\].
We can write the given equation as \[2{x^2} + 4x + 4x + 8 = 0\], where \[{b_1} = 4\] and \[{b_2} = 4\]. Also \[{b_1} \times {b_2} = 4 \times 4 = 16(ac)\] and \[{b_1} + {b_2} = 4 + 4 = 8(b)\].
Thus we have,
\[ \Rightarrow 2{x^2} + 8x + 8 = 2{x^2} + 4x + 4x + 8\]
\[ = 2{x^2} + 4x + 4x + 8\]
Taking ‘2x’ common in the first two terms and taking 4 common in the remaining two terms we have,
\[ = 2x\left( {x + 2} \right) + 4(x + 2)\]
Again taking \[\left( {x + 2} \right)\] common we have,
\[ = \left( {x + 2} \right)\left( {x + 2} \right)\]
Hence the factors of \[2{x^2} - 6x + 4 = 0\] are \[\left( {x + 2} \right)\] and \[\left( {x + 2} \right)\].
(We can also find the roots of the given quadratic equation by equating the obtained factors to zero. That is
\[\left( {x + 2} \right)\left( {x + 2} \right) = 0\]
By zero product principle we have,
\[\left( {x + 2} \right) = 0\] or \[\left( {x + 2} \right) = 0\]
\[x = - 2\] or \[x = - 2\]these are the roots)
Note: We can easily solve this if we know some idea of algebraic identity,
\[2{x^2} + 8x + 8 = 0\]
We can divide the whole equation by 2, to make it simple
\[{x^2} + 4x + 4 = 0\]
But we know \[{(a + b)^2} = {a^2} + 2ab + {b^2}\], applying this we have,
\[{(x + 2)^2} = 0\]
Hence the factors of \[2{x^2} - 6x + 4 = 0\] are \[\left( {x + 2} \right)\] and \[\left( {x + 2} \right)\]
These are the roots of the given polynomial of degree 2. In above, if we are unable to expand the middle term of the given equation into a sum of two numbers then we use a quadratic formula to solve the given problem. Quadratic formula and Sridhar’s formula are both the same. Careful in the calculation part.
Complete step-by-step solution:
Given, \[2{x^2} + 8x + 8 = 0\]
Since the degree of the equation is 2, we have 2 factors.
On comparing the given equation with the standard quadratic equation\[a{x^2} + bx + c = 0\], we have\[a = 2\], \[b = 8\] and \[c = 8\].
The standard form of the factorization of quadratic equation is \[a{x^2} + {b_1}x + {b_2}x + c = 0\], which satisfies the condition \[{b_1} \times {b_2} = a \times c\] and \[{b_1} + {b_2} = b\].
We can write the given equation as \[2{x^2} + 4x + 4x + 8 = 0\], where \[{b_1} = 4\] and \[{b_2} = 4\]. Also \[{b_1} \times {b_2} = 4 \times 4 = 16(ac)\] and \[{b_1} + {b_2} = 4 + 4 = 8(b)\].
Thus we have,
\[ \Rightarrow 2{x^2} + 8x + 8 = 2{x^2} + 4x + 4x + 8\]
\[ = 2{x^2} + 4x + 4x + 8\]
Taking ‘2x’ common in the first two terms and taking 4 common in the remaining two terms we have,
\[ = 2x\left( {x + 2} \right) + 4(x + 2)\]
Again taking \[\left( {x + 2} \right)\] common we have,
\[ = \left( {x + 2} \right)\left( {x + 2} \right)\]
Hence the factors of \[2{x^2} - 6x + 4 = 0\] are \[\left( {x + 2} \right)\] and \[\left( {x + 2} \right)\].
(We can also find the roots of the given quadratic equation by equating the obtained factors to zero. That is
\[\left( {x + 2} \right)\left( {x + 2} \right) = 0\]
By zero product principle we have,
\[\left( {x + 2} \right) = 0\] or \[\left( {x + 2} \right) = 0\]
\[x = - 2\] or \[x = - 2\]these are the roots)
Note: We can easily solve this if we know some idea of algebraic identity,
\[2{x^2} + 8x + 8 = 0\]
We can divide the whole equation by 2, to make it simple
\[{x^2} + 4x + 4 = 0\]
But we know \[{(a + b)^2} = {a^2} + 2ab + {b^2}\], applying this we have,
\[{(x + 2)^2} = 0\]
Hence the factors of \[2{x^2} - 6x + 4 = 0\] are \[\left( {x + 2} \right)\] and \[\left( {x + 2} \right)\]
These are the roots of the given polynomial of degree 2. In above, if we are unable to expand the middle term of the given equation into a sum of two numbers then we use a quadratic formula to solve the given problem. Quadratic formula and Sridhar’s formula are both the same. Careful in the calculation part.
Recently Updated Pages
What percentage of the area in India is covered by class 10 social science CBSE
The area of a 6m wide road outside a garden in all class 10 maths CBSE
What is the electric flux through a cube of side 1 class 10 physics CBSE
If one root of x2 x k 0 maybe the square of the other class 10 maths CBSE
The radius and height of a cylinder are in the ratio class 10 maths CBSE
An almirah is sold for 5400 Rs after allowing a discount class 10 maths CBSE
Trending doubts
The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths
Why is there a time difference of about 5 hours between class 10 social science CBSE
Change the following sentences into negative and interrogative class 10 english CBSE
Write a letter to the principal requesting him to grant class 10 english CBSE
Explain the Treaty of Vienna of 1815 class 10 social science CBSE
Write an application to the principal requesting five class 10 english CBSE